Efficient synthesis of (S, R)-Bn-Yanphos and Rh/(S, R)-Bn-Yanphos catalyzed asymmetric hydroformylation of vinyl heteroarenes. Issue 2 (6th December 2016) - Wei, Biao; Chen, Caiyou; You, Cai; Lv, Hui; Zhang, Xumu
Abstract : ( S, R )-Bn-Yanphos/Rh-catalyzed asymmetric hydroformylation of vinyl heteroarenes and allyl-1 H -indole has been achieved, affording the corresponding α-heteroaryl aldehydes with high enantioselectivities. Abstract : A concise and efficient synthesis of ( S, R )-Bn-Yanphos on a gram scale has been developed. When ( S, R )-Bn-Yanphos was employed in Rh-catalyzed asymmetric hydroformylation of vinyl heteroarenes and allyl-1 H -indole, it exhibited excellent catalytic activity, affording chiral heteroaryl aldehydes in good yields with high regio- and enantioselectivities (up to 96% ee).